Pentahelix Collaboration In The Implementation Of Agricultural Policies For Regional Food Security: A Study In The Harvest Failure-Prone Area Of Kaway Xvi District, West Aceh Regency - Pratama, Agus; jalaluddin, Jalaluddin; Safrida, Safrida; Mardhiah, Nellis; Maulida, Desi (Universitas Riau Kepulauan, 2025)
This study is novel in that it examines the pentahelix collaboration model in the context of regional food policy. Until now, similar studies have been limited to sectoral approaches and have not focused on areas prone to crop failure in strengthening food security, which is a research gap. The main objective of this study is to determine how the pentahelix collaboration model is implemented in agricultural policy for food security in West Aceh Regency. The method used is a qualitative case study approach. The results show that the form of pentahelix collaboration can be seen from the roles of various actors. The theoretical contribution can expand and enrich the application of the pentahelix concept by adding a focus on crop failure, agrarian risks, and food security in the collaborative concept. Meanwhile, the practical contribution through the research results serves as a guide for the government in strengthening the collaborative concept. The essence of pentahelix is to carry out a coordinating function in food agriculture policy. The weakness of implementing agricultural policy through the pentahelix approach in West Aceh is the lack of specific regulations, such as standard operating procedures that regulate the flow of collaboration across actors. The limitations of the study are evident in the limited perspectives of the actors. A recommendation for the future is to create and establish a cross-actor forum to serve as a platform for disseminating information on agricultural food in West Aceh.